2008
DOI: 10.1097/tp.0b013e318186b7fb
|View full text |Cite
|
Sign up to set email alerts
|

Cinacalcet Increases Calcium Excretion in Hypercalcemic Hyperparathyroidism After Kidney Transplantation

Abstract: We provide evidence that the calcium lowering effect of cinacalcet in patients with persistent hyperparathyroidism after kidney transplantation is caused, at least in part, by increased urinary calcium excretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 35 publications
3
28
0
2
Order By: Relevance
“…Two studies reported a temporary increase in the fractional excretion of calcium following cinacalcet treatment [22,37], another observed a sustained increase [38]. The present study shows a continuous and marked increase in both fractional excretion of calcium and urinary calcium/creatinine ratio in morning urine samples from fasting patients.…”
Section: Discussionsupporting
confidence: 58%
“…Two studies reported a temporary increase in the fractional excretion of calcium following cinacalcet treatment [22,37], another observed a sustained increase [38]. The present study shows a continuous and marked increase in both fractional excretion of calcium and urinary calcium/creatinine ratio in morning urine samples from fasting patients.…”
Section: Discussionsupporting
confidence: 58%
“…However, its use in kidney transplant recipients remains off-label. Several prospective [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and retrospective [31][32][33][34][35][36][37][38][39][40][41] observational cohort studies have examined the potential effects of cinacalcet in kidney transplant recipients. Most of these studies have included small cohorts with short follow-up periods, whereas only 4 studies have reported follow-up of greater than 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…и соавт. [16], исчезно-вение гиперкальциемии, сопровождающей пост-трансплантационный ГПТ, происходит вследствие уменьшения реабсорбции кальция в петле Генле и увеличения его мочевой экскреции на фоне сниже-ния плазменной концентрации ПТГ, хотя не у всех, в том числе и наших, пациентов обнаруживалась та-кая взаимосвязь. Очень вероятно, что нормализация сывороточного кальция наступает в результате по-давления интенсивности костного метаболизма на фоне снижения секреции ПТГ [7,12].…”
Section: комментарийunclassified